On some aspects of distribution of meso-scale systems In Madhya Maharashtra and Marathwada during Monsoon season - SAXENA, VP; AGRAWAL, ASHALATA (MAUSAM, 1988)
The pockets :of heavy rainfall in a widespread rainfall system during the southwest monsoon period in the Indian region are the centres of meso-scale systems. Contingency index technique is applied to determine the diameters of such systems and their distribution over Madhya Maharashtra and Marathwada sub-divisions of Maharashtra during the monsoon period. The technique determines the probability or otherwise of occurrence of rainfall of similar intensity at pairs of stations at different distances. The variation of CI with distance gives an indication of distribution of meso-scale cloud systems embedded in macro-scale systems. The method eliminates the random chance of occurrence of similar type of precipitation over stations having the same CI.